Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T17:53:35+01:00
1. Przekształć ilorazy na sumy:
a) -4(x + y) = -4x-4y
b) -3a( ⅓ - a ) = -a+3a
c) ½(2a - 4b +1) = a-2b+½
d) 3p(2r +5p - 1) = 6pr+15p²-3p
2. Zapisz w jak najprostszej postaci:
a(a + b + c) - b(a - b + c)- c( a - b - c) =a²+ab+ac-ab+b²-bc-ac+bc+c²= a²+b²+c²
4 5 4
2010-03-10T17:53:55+01:00
1. Przekształć ilorazy na sumy:
a) -4(x + y) = -4x-4y
b) -3a( ⅓ - a ) = -a+3a^2 (do kwadratu)
c) ½(2a - 4b +1) = a-2b+½
d) 3p(2r +5p - 1) = 6pr+15p^2 - 3p
2. Zapisz w jak najprostszej postaci:
a(a + b + c) - b(a - b + c)- c( a - b - c) = a^2+ab+ac-ab+b^2-bc-ac+bc+c^2 = a^2 + b^2 + c^2

4 5 4